Desain Sistem Informasi Remind Dialysis Guna Menunjang Tata Kelola Klinis Hemodialisa Berbasis Web - Fadliyyah, Helfy; Syahidin, Yuda; Suryani, Ade Irma (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The most important factor in determining an individual's level of productivity in daily life is their health. For this reason, every year on March 10th, we celebrate it as National Ginjal Day. Numerous factors contribute to patients' difficulties in undergoing hemodialysis, as well as increasing the number of hemodialysis patients who are in productive states and have positive symptoms. This situation calls for a system that can alert patients to the need for efficient and effective hemodialysis. Wawancara and Pustaka's studies are used by researchers to gather data, together with descriptively applied qualitative analysis. The waterfall method is used by researchers to develop new systems. The results of system testing using approved methods can increase patient care's effectiveness and efficiency in helping patients with hemodialysis. In addition, this information system can improve patient care and the standard of living in sick rooms.